Body Structure and the Maturity Rate of Girls in Wrocław - Janusz, Antoni; Jarosińska, Aniela; Stęślicki, Jerzy (Anthropological Review, 1985)
Differences in the somatic structure between early and late maturing girls were investigated. The examinations were re peated three times in the age of 15, 16 and 17 years. Changes in the somatotype were found to correlate with age.